Vegetation extraction in riparian zones based on UAV visible light images and marked watershed algorithm - Ma, Yuanjie; Chen, Xu; Zhang, Yaping (Frontiers in Earth Science, 2024)
The riparian zone is an area where land and water are intertwined, and vegetation is rich and complexly distributed. The zone can be directly involved in ecological regulation. In order to protect the ecological environment of the riparian zone, it is necessary to monitor the distribution of vegetation. However, there are many disturbing factors in extracting riparian vegetation, the most serious of which are water bodies with similar colours to the vegetation. To overcome the influence of water bodies on vegetation extraction from UAV imagery of riparian areas, this paper proposes a novel approach that combines the marked watershed algorithm with vegetation index recognition. First, the image is pre-segmented using edge detection, and the output is further refined with the marked watershed algorithm. Background areas are classified as potential regions for vegetation distribution. Subsequently, the final vegetation distribution is extracted from these potential vegetation areas using the vegetation index.The segmentation threshold for the vegetation index is automatically determined using the OTSU algorithm. The experimental results indicate that our method, when applied to UAV aerial imagery of the riparian zone, achieves an overall accuracy of over 94%, a user accuracy of over 97%, and a producer accuracy of over 93%.